Finite element modelling of the Swiss plate geophone bedload monitoring system. Issue 5 (3rd September 2022) - Chen, Zheng; He, Siming; Nicollier, Tobias; Ammann, Lorenz; Badoux, Alexandre; Rickenmann, Dieter
ABSTRACT: Drop experiments with quartz spheres in a flume setting were performed to investigate the dynamic signal response of the Swiss plate geophone bedload monitoring system for varying particle size, vertical impact velocity, and impact location. For a similar sphere impact set-up, the finite element method was used to determine the propagation characteristics of the stress wave in the structure of the monitoring system. The experimental and numerical results showed a qualitative and partially quantitative agreement in the changes in the number of signal impulses per particle mass, the amplitude, and the centroid frequency with increasing colliding sphere size. These parameters characterizing the geophone vibrations also showed qualitatively similar dependencies with increasing bedload size as field measurements show with natural particles and a theoretical model. The findings of this study contribute to the understanding of the signal response of the monitoring system, which may result in improving bedload grain size classifications.